2008
DOI: 10.1002/fuce.200700059
|View full text |Cite
|
Sign up to set email alerts
|

Durability of ABPBI‐based MEAs for High Temperature PEMFCs at Different Operating Conditions

Abstract: High temperature PEMFCs based on phosphoric acid‐doped ABPBI membranes have been prepared and characterised. At 160 °C and ambient pressure fuel cell power densities of 300 mW cm–2 (with hydrogen and air as reactants) and 180 mW cm–2 (with simulated diesel reformate/air) have been achieved. The durability of these membrane electrode assemblies (MEAs) in the hydrogen/air mode of operation at different working conditions has been measured electrochemically and has been correlated to the cell resistivity, the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 27 publications
9
77
1
Order By: Relevance
“…0.2 g m −2 s −1 ) at the cathode but only initially an acid loss (also ca. 0.2 g m −2 s −1 ) at the anode [240,260]. This was confirmed by the nearly constant resistance through the test period of 1000 h, indicating that the acid loss does not seem to be the main reason for the performance degradation.…”
Section: Steady-state Operation and Acid Lossmentioning
confidence: 87%
See 1 more Smart Citation
“…0.2 g m −2 s −1 ) at the cathode but only initially an acid loss (also ca. 0.2 g m −2 s −1 ) at the anode [240,260]. This was confirmed by the nearly constant resistance through the test period of 1000 h, indicating that the acid loss does not seem to be the main reason for the performance degradation.…”
Section: Steady-state Operation and Acid Lossmentioning
confidence: 87%
“…With acid-doped AB-PBI, however, Wannek et al [260] reported a high degradation rate of 20-25 V h −1 under constant load. By collecting the acid from the offgas through a water condenser, they observed a constant acid loss (ca.…”
Section: Steady-state Operation and Acid Lossmentioning
confidence: 99%
“…The main problems reported in the literature are the loss in the catalyst active area due to catalyst agglomeration, and phosphoric acid leaching out from the cell [37,119,120]. It is the opinion of Yu et al [121] and Wannek et al [122] that the main source of performance loss is due to catalyst agglomeration.…”
Section: Degradationmentioning
confidence: 99%
“…[14][15][16] In the higher end of the operating temperature regime (180-200 °C) the PA loss rate increases considerably, eventually leading to acid depletion and proton conductivity decay. 6,17 High water activities, i.e. operation at high current loads, further promote this mechanism, 6,18 due to suppressed pyrophosphate formation.…”
mentioning
confidence: 99%